2000
DOI: 10.1210/jcem.85.4.6554
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Incidence and Spectrum of Thyroid Carcinoma in Tasmania (1978–1998) during a Transition from Iodine Sufficiency to Iodine Deficiency1

Abstract: Exposure to ionizing radiation, changing levels of iodine nutrition, and increased pathologic diagnosis of clinically unimportant thyroid neoplasia have all been proposed as explanations for a worldwide rise in the incidence of thyroid carcinoma (TC) over the past 6 decades. Tasmania is geographically an area of endemic iodine deficiency. In this report, we describe the spectrum of TC in a population averaging 450,000 persons during a 21-yr period that spans the communities transition from iodine sufficiency t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Some countries have introduced iodized salt programs and have since observed increasing trends of TC (1, 5762), while other countries have not introduced these programs or observed a decrease in iodine intake although the incidence of TC continues to increase here as well (3, 63). …”
Section: Discussionmentioning
confidence: 99%
“…Some countries have introduced iodized salt programs and have since observed increasing trends of TC (1, 5762), while other countries have not introduced these programs or observed a decrease in iodine intake although the incidence of TC continues to increase here as well (3, 63). …”
Section: Discussionmentioning
confidence: 99%
“…High iodine in diet has been associated with thyroiditis, hypothyroidism, hyperthyroidism, increased risk of papillary carcinoma, and decreased risk of follicular carcinoma [30,31]. In this study, there was a smaller number of follicular carcinomas and no trends were observed in children and AYAs.…”
Section: Plos Onementioning
confidence: 45%
“…The role of iodine in the pathogenesis of thyroid cancer is controversial, and the difference has been documented according to tumor histology. Iodine deficiency is associated with follicular carcinoma, whereas excess iodine increases the risk of papillary type of thyroid cancer [30].…”
Section: Plos Onementioning
confidence: 99%
“…To verify that high iodine contributes to the cell cycle distribution in PTC cells, DNA content was measured (Burgess et al 2000) by flow cytometry. We observed that treatment of PTC cells with 10 −3 M NaI enhanced the proportion of cells in the G0/G1 phase compared to that in control cells (Fig.…”
Section: −3 M Nai Reduces Viability and Proliferation In Ptc Cellsmentioning
confidence: 99%